CONCEPT OF ACCIDENT AND INJURY OF AIR PASSENGERS - Đurđev, Dušanka (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
Despite the efforts from the international community to create an unified liability regime in Private International Air Law, there are still significant hurdles to be overcome. Many essential rules from this legal regime are vague and open to interpretation. The role of judges is crucial in order to give them their intended meaning. Thus, this paper examines jurisprudence concerning carrier liability in case of death or injury of passengers.